Medium-term Effects of Enhanced External Counterpulsation in the Structural and Functional Parameters of Blood Vessels in Patients with Coronary Artery Disease - K. S. Karaganov; O. A. Slepova; A. S. Lishuta; N. I. Solomakhina; Yu. N. Belenkov (Рациональная фармакотерапия в кардиологии)
Aim. To study the mid-term effects of enhanced external counterpulsation (EECP) in the structural and functional parameters of blood vessels, exercise tolerance and quality of life indicators in patients with verified coronary artery disease (CAD).Material and methods. Patients (n=70) with verified stable CAD (angina pectoris class II-III) complicated by chronic heart faillure class II-III (NYHA) were included in the study. Data from 65 patients (48 to 74 years old; 45 men and 20 women) are included in the final analysis. All patients had a course of EECP (35 hours procedures with a compression pressure of 220-280 mm Hg). All patients at baseline, 3 and 6 months later had a 6 walk minute test (6WMT), an assessment of the clinical status, quality of life of patients (Minnesota Living with Heart Failure Questionnaire, SF-36). Computer nailfold video capillaroscopy, photoplethysmography with pulse wave recording and contour analysis, applanation tonometry to assess central aortic systolic pressure and radial augmentation index were performed to assess the structural and functional state of large and microcirculatory vessels.Results. Significant improvement in exercise tolerance both after 3 and after 6 months (increase in distance in 6WMT by 44.6% after 3 months and 34.3% after 6 months, p <0.05), improved quality of life (increased overall score on the SF-36 questionnaire from 50.3±8.1 to 59.8±8.8, p<0.05), an increase in the left ventricular ejection fraction were found. Significant improvement in indicators showing the function of the endothelium of both large vessels (phase shift: from 5.6 [2.45; 7.3] to 6.8 [3.1; 8.1] m / s) and microcirculatory vessels (occlusion index: from 1.51 [1.21; 1.7] to 1.66 [1.2; 1.9]), as well as a decrease in functional disorders of the capillary bed of the skin (% of perfused capillaries, density of the capillary network in the test with reactive hyperemia) were found after 3 months. However, after 6 months, there were no significant changes in these parameters compared to the baseline value. No significant change in indicators showing structural remodeling of both large vessels and microcirculatory vessels was found.Conclusion. The positive effect of the EECP course on the functional status (exercise tolerance) and quality of life in patients with stable coronary artery disease complicated by chronic heart faillure was found both after 3 and 6 months. Positive dynamics of the functional state of large vessels and microvasculature was found only after 3 months.